Effects of Radioiodine Treatment on Salivary Gland Function in Patients with Differentiated Thyroid Carcinoma: Experience at INMAS, Mitford (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Radioiodine therapy is very effective and popular method of choice for the treatment of carcinoma thyroid. Dry mouth is acommon side effects after radioiodine therapy and sequel of the salivary gland dysfunction. Many of the patients are suffering from this side effect. This study was designed to evaluatethe functionof the salivary gland of the patients treated with radioiodine therapy.Materials and methods: This cross sectional study was done in the Institute of Nuclear Medicine and Allied Sciences Mitford Dhaka for about 06 months from August 2019 to March 2020. About 51 patients were enrolled for this study having single dose of radioiodine therapy. Dynamic sialo scintigraphy with citrus stimulation was done after intravenous injection of 02 mci of Tc-99m. After 10 minutes of dynamic study lemon juice was given orally for the augmentation of the gland function. Result was interpreted as salivary gland dysfunction when a curve was uprising after lemon juice augmentation and normal functioning when fall off curve. Then data were compiled and analyzed by SPSS version 22.Results: The mean age of the study subjects were 35.1 ± 9.8, age ranged from 14~56 years, sixwere male and 45 were female participants. The mean dose was 4.3±1.1GBq, ranges from 1.8~7.4GBq. The proportion of salivary gland dysfunction was 60.8% while 39.2% had normal salivary gland function.Right salivary gland dysfunction was found in52.9% patients while 54.9% patient showed left salivary gland dysfunction. A little above a decile (13.7%) showed right submandibular gland dysfunction while a little less than that(7.8%) showed left submandibular gland dysfunction. Salivary gland dysfunction was related to the dose of the radioiodine therapy (p